Degradation of Strength and Stiffness of Sandstones Caused by Wetting-Drying Cycles: The Role of Mineral Composition. (1st October 2021) - Chen, Lu; Rui, Yichao; Zhao, Yihan
Abstract : Rock mechanical parameters are of great importance for the construction and design of rock engineering. Rocks are usually subjected to the deteriorating effect of cyclic wetting-drying because of the change in moisture content. The main objective of this study is to reveal the degradation effects of wetting-drying cycles on strength and modulus on varying rocks. Three kinds of sandstones with different mineral constituents are selected for testing. Artificial treatments of cyclic wetting-drying are conducted on respective specimens of the three sandstones (0, 10, 20, 30, and 40 cycles) to simulate the damage of rocks exposed to natural weathering. Uniaxial compressive tests are carried out on sandstone specimens to obtain their strength and modulus. Test results show that, for the tested sandstones, both of the uniaxial compressive strength (UCS) and modulus are reduced as the cyclic number rises. In the first ten cycles, the losses of UCS and modulus are very significant. Subsequently the changes of UCS and modulus become much more placid against cyclic number. When the cyclic number is the same, the loss percentages of rock mechanical properties of the three sandstones are very different which mainly depends on the contents of expandable and soluble minerals.